The undevelopment areas and the environmental impacts about it in the right side from Mosul city - Al-Zaidy, Nashwan Mahmmoud (Al-Adab Journal, 2020)
The foundation of undevelopment urban areas , their expansion and features which differentiated have left effects on Mosul environment which are varied with the variation of those features . These effects carry essential indicators that have an importance because they shed light on problems which they suffer from those areas and they also shed light on problems that add to the city , the most important problems that should be resolved are showed through that.